1987
DOI: 10.1063/1.527566
|View full text |Cite
|
Sign up to set email alerts
|

Generalized quasispin for supergroups

Abstract: The embedding of the dynamical algebra U(M/N) of nuclear supersymmetries in larger algebraic structures is studied. A noncompact Z2⊕Z2 graded color superalgebra SpO(2M/1/2N/0) is identified as a receptacle for various chains containing boson and fermion (super) algebras. The existence of a generalized quasispin algebra is demonstrated and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…. , n. In each multiplet its component fields x i , ψ i , ξ i , z i transform according to (23). An invariant sigmamodel action S int , describing the motion of interacting multiplets, can be defined through the position…”
Section: Invariant Actions For the (2 2 0) Root Multipletmentioning
confidence: 99%
See 1 more Smart Citation
“…. , n. In each multiplet its component fields x i , ψ i , ξ i , z i transform according to (23). An invariant sigmamodel action S int , describing the motion of interacting multiplets, can be defined through the position…”
Section: Invariant Actions For the (2 2 0) Root Multipletmentioning
confidence: 99%
“…After the introduction [17][18][19][20] of Z 2 × Z 2 -graded Lie superalgebras, a long history of investigations of Z 2 × Z 2 (and higher) graded symmetries in physical problems, which recently attracted a renewed interest, began. Several works considered enlarged symmetries in various contexts such as extensions of spacetime symmetries (beyond ordinary de-Sitter and Poincaré algebras), supergravity theory, quasispin formalism, parastatistics and non-commutative geometry, see [21][22][23][24][25][26][27][28][29][30]. It was also recently revealed that the symmetries of the Lévy-Leblond equation, which is a nonrelativistic quantum mechanical wave equation for spin 1/2 particles, are given by a Z 2 × Z 2 -graded superalgebra [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The natural graded structure when both fermionic and bosonic oscillator modes are present, where closure on both linear and bilinear combinations is required, is indeed that of a Z 2 × Z 2 graded colour superalgebra. See[15] and references therein 8. Following the arguments of §2 above, in this case there are potentially 8 couplings, or 7 arbitrary coefficients up to normalisation (see §A.1 and (20) below).…”
mentioning
confidence: 99%
“…The color (super)algebras have been an objects of interest in mathematics for the last four decades, and many works such as classification of the algebras under some conditions, representations, cohomology and so on, have been done [5,6,7,8,9,10,11,12,13,14,15,16,17] (and references therein). On the other hand, physical applications are very limited [18,19,20,21,22,23,24,25] so one may conclude that color (super)algebras are not widely known in the physics community.…”
Section: Introductionmentioning
confidence: 99%